(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
As is known, the human body, in addition to adapting to physical activity, continuously adapts to various factors and environmental conditions, such as psychogenic stress, changes in the nutritional composition of water and diet, high-altitude hypoxia, and weather and seasonal dynamics of environmental conditions. Therefore, studying the patterns of adaptation to several biotropic factors is relevant. The effect of the body’s adaptation to physical activity largely depends on the functioning of the circulatory system and the immune system. However, adaptive changes in circulatory function during adaptation to physical activity during seasonal dynamics of environmental conditions have not been described in the available literature and require further study. On the other hand, it is known that the body’s adaptation to stressful effects of various environmental factors is largely determined by the state of the blood and immune systems.